Composite cathode comprising polymer electrolyte and nickel-based cathode active material
By using polymer electrolytes containing deep eutectic solvents and specific polymer networks, the safety and environmental problems of liquid electrolytes in existing lithium secondary batteries are solved, and good compatibility and cyclic stability with high potential cathode materials are achieved.
Patent Information
- Application Number
- CN202380065802.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-19
- Filing Date
- 2023-09-18
- Publication Date
- 2025-04-11
AI Technical Summary
The existing lithium secondary batteries use liquid electrolytes, which pose safety risks and environmental pollution risks. It is also difficult to develop solid composite electrolytes compatible with high-potential cathode materials.
The electrolyte composition is encapsulated by polymerizing a polymer network containing a specific (meth)acrylamide monomer using a polymer electrolyte containing a deep eutectic solvent and compatible with a cathode active material containing Li, Ni, Mn, Co.
It achieves excellent cycle stability with high potential cathode materials, provides a solid-state lithium-ion battery with high safety and environmentally friendly, and reduces EHS hazards.
Smart Images

Figure CN119816951A_ABST
Abstract
Description
[0001] Technical Field and Background Art
[0002] The present invention relates to a composite cathode comprising a polymer electrolyte and a cathode active material, wherein the cathode active material comprises Li, M and O, wherein M comprises Ni and comprises one or both of Mn and Co. The polymer electrolyte comprises an electrolyte composition, wherein the electrolyte composition comprises a deep eutectic solvent (DES) and a polymer network having a polyacrylamide backbone.
[0003] In recent years, the development of small, lightweight electronic products, electronic equipment and communication equipment is rapid. Similarly, electric vehicles have been widely adopted, which have appeared as environmentally attractive means of transportation. These factors lead to the demand for improved performance of the secondary storage battery used as the power source in the product. In addition, lithium secondary storage battery becomes a high-performance storage battery that attracts attention due to its high energy density and high reference electrode potential.
[0004] Conventional lithium secondary batteries contain liquid electrolytes, such as organic solvents. A significant disadvantage of liquid electrolytes is that the constituent components, particularly the solvents, are flammable, which poses a significant safety risk during normal operation, particularly in the event of an accident. Another disadvantage is inherent in the liquid nature of the electrolyte, which is associated with an increased risk of leakage and, in the event of a spill or leak, of environmental contamination.
[0005] Recently, efforts have been made to develop solid electrolytes that allow solid-state lithium-ion batteries to be provided. Such solid-state batteries have significantly reduced EHS (environmental, health and safety) hazards. Conventional solid electrolytes may include oxide-based solid electrolytes, polymer-based solid electrolytes, and sulfide-based electrolytes. Polymer-based electrolytes are commonly used due to their low flammability, good flexibility, excellent thermal stability, and high safety.
[0006] The difficulty in developing solid electrolytes with high ionic conductivity, wide electrochemical window, and mechanical / thermal stability has led to the concept of solid-liquid composite materials, such as solid composite electrolytes (SCEs). These electrolytes contain a liquid lithium-ion conducting electrolyte enclosed within a solid backbone or network. Examples include ionic liquids confined within an inorganic (e.g., silica) or polymer (e.g., poly(ethylene glycol) diacrylate (PEODA)) solid backbone.
[0007] The main challenge in the production of solid composite electrolytes is to select a polymer backbone that is stable to sol-gel synthesis and can effectively encapsulate liquid lithium-ion electrolytes. In addition, it is difficult to develop solid composite electrolytes that are compatible with high potential cathode materials (such as NMC622 or NMC811) and exhibit satisfactory anode stability. For example, the most common solid polymer electrolyte PEO (polyethylene oxide) has a limited electrochemical performance of about 4.0 V vs. Li + / Li potential anode stability.
[0008] Energy Environ. Sci., 2021, 14, pp. 931-939 considers the use of alkali metal bis(trifluoromethane)-sulfonyl imide (TFSI) salts in polymer electrolytes containing N-isopropylacrylamide (NIPAM) polymer backbones.
[0009] Chem.Mater.2020, 32, pp. 3783-3793 considers the use of deep eutectic solvents based on lithium bis(trifluoromethane)-sulfonyl imide (LiTFSI) and N-methylacetamide (MAc) in polymer electrolytes containing ethylene glycol 4-acryloylmorpholine (AcMo) backbones.
[0010] US2020 / 0343586A1 considers the use of various deep eutectic solvents in polymer electrolytes containing various polymer backbones. A polymer electrolyte containing a deep eutectic solvent based on lithium bis(trifluoromethane)sulfonyl imide (LiTFSI) and N-methylacetamide (MAc) in a polymer network containing an acrylate backbone is exemplified.
[0011] It is an object of the present invention to provide a composite cathode comprising a polymer electrolyte comprising a polymer network that is compatible with a deep eutectic solvent.
[0012] Another object of the present invention is to provide a composite cathode comprising a polymer electrolyte that is compatible with high voltage cathode active materials, particularly NMC622.
[0013] Another object of the present invention is to provide a composite cathode comprising a polymer electrolyte having high anode stability.
[0014] Another object of the present invention is a composite cathode comprising a polymer electrolyte having good mechanical flexibility. Summary of the invention
[0015] The present inventors have found that polymer electrolytes comprising a polymer network based on a specific (meth)acrylamide monomer effectively encapsulate a deep eutectic solvent (DES) and are surprisingly compatible with electrode active materials comprising Li, M and O, wherein M comprises Ni and comprises one or both of Mn and Co. As shown in the accompanying examples, the polymer electrolytes described herein are found to have excellent cycling stability when combined with high potential electrode active materials such as NMC622. In addition, the present inventors have found that the polymer electrolytes can be synthesized in the presence of a cathode active material, thereby providing a composite cathode material. One or more objects of the present invention are achieved by the different aspects of the present invention as described herein.
[0016] Thus, in a first aspect of the present invention, there is provided a composite cathode comprising a cathode active material and a polymer electrolyte, wherein the cathode active material comprises Li, M and O, wherein M comprises Ni and comprises one or both of Mn and Co, wherein the polymer electrolyte comprises an electrolyte composition and a polymer network, wherein the electrolyte composition preferably comprises a deep eutectic solvent (DES), wherein the polymer electrolyte is obtainable by polymerizing a precursor composition comprising the electrolyte composition and a first monomer according to formula (I)
[0017]
[0018] in
[0019] R 1 represents a first substituent having 1 to 8 carbon atoms and optionally comprising at least one functional group selected from alcohol, amine, ether, ketone, amide, acetal, ketal, aminoacetal, hemiaminal ether or a combination thereof, preferably wherein R 1 Selected from C1-C6 alkyl, C1-C6 hydroxyalkyl, -(CH2-CH2-O) n -H;
[0020] and
[0021] Where R 2 represents H or a second substituent having 1 to 8 carbon atoms and optionally comprising at least one functional group selected from alcohol, amine, ether, ketone, amide, acetal, ketal, aminoacetal, hemiaminal ether or a combination thereof, preferably wherein R 2 Selected from H, C1-C6 alkyl, C1-C6 hydroxyalkyl, -(CH2-CH2-O) n -H;
[0022] Where R 3 is selected from H, methyl or ethyl; and
[0023] wherein n is an integer from 1 to 5.
[0024] The precursor composition generally further comprises a first crosslinking agent. Preferably, the first crosslinking agent is selected from a crosslinking agent comprising two or more functional groups selected from the group consisting of: allyl (-CH3-CH=CH2), oxirane (-C2H3O), glycidyl (-CH2-C2H3O), vinyl ether (-O-CH=CH2), vinyl ester (-C(O)-O-CH=CH2), vinyl amide (-C(O)-NH-CH=CH2), vinyl amine (-NH-CH=CH2), norbornene, maleate, fumarate, itaconate, alkynyl (-C≡CH), styrene (-Ph-CH=CH2), acrylamide (-NH-C(O)-CH =CH2), methacrylamide (-NH-C(O)-C(CH3)=CH2), acrylate (-OC(O)-CH=CH2), methacrylate (-OC(O)-C(CH3)=CH2) and combinations thereof, preferably the first cross-linking agent is selected from a cross-linking agent comprising two or more functional groups selected from the group consisting of acrylamide (-NH-C(O)-CH=CH2), methacrylamide (-NH-C(O)-C(CH3)=CH2), acrylate (-OC(O)-CH=CH2), methacrylate (-OC(O)-C(CH3)=CH2) and combinations thereof.
[0025] In another aspect of the present invention, there is provided a method for producing a composite cathode, the method comprising the steps of:
[0026] (a1) providing a cathode active material in a particle form, the cathode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co;
[0027] (b1) providing a polymer electrolyte as described herein in particle form;
[0028] (c1) blending the cathode active material of step (a) and the polymer electrolyte of step (b) into a uniform blend; and
[0029] (d1) Optionally, compacting the blend obtained in step (c).
[0030] In another aspect of the present invention, there is provided a method for producing a composite cathode, the method comprising the steps of:
[0031] (a2) providing a cathode active material, the cathode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co;
[0032] (b2) providing a precursor composition as described herein;
[0033] (c2) contacting the precursor composition with the cathode active material; and
[0034] (d2) polymerizing the precursor composition in the presence of the cathode active material.
[0035] In another aspect of the invention, there is provided use of a composite cathode of the invention as a component of an electrochemical cell.
[0036] In another aspect of the invention, there is provided an electrochemical cell comprising an anode and a composite cathode of the invention.
[0037] In another aspect of the invention, there is provided a battery, more particularly a lithium ion battery or a lithium metal battery, comprising at least one electrochemical cell as described herein, for example two or more electrochemical cells according to the invention.
[0038] In another aspect of the invention, there is provided a method of manufacturing or operating an automobile, a computer, a personal digital assistant, a mobile phone, a watch, a camcorder, a digital camera, a thermometer, a calculator, a laptop BIOS, a communication device, a remote car lock, and a stationary application (such as an energy storage device for a power plant) by using at least one storage battery or at least one electrochemical cell as described herein.
[0039] In another aspect of the present invention, there is provided a use of an electrochemical cell comprising a composite cathode of the present invention in a motor vehicle, a bicycle operated by an electric motor, a robot, an aircraft (e.g., an unmanned aerial vehicle including a drone), a ship, a satellite, or a stationary energy storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Anodic linear sweep voltammetry performed on the polymer electrolyte of Example 1 is shown.
[0041] Figure 2 Anodic linear sweep voltammetry performed on the polymer electrolyte of Example 2 is shown.
[0042] Figure 3 Anodic linear sweep voltammetry performed on the polymer electrolyte of Example 3 is shown.
[0043] Figure 4 Anodic linear sweep voltammetry performed on the polymer electrolyte of Example 4 is shown.
[0044] Figure 5 Anodic linear sweep voltammetry performed on the polymer electrolyte of Example 5 is shown.
[0045] Figure 6Anodic linear sweep voltammetry performed on the polymer electrolyte of Comparative Example 6 is shown.
[0046] Figure 7 Anodic linear sweep voltammetry performed on the polymer electrolyte of Comparative Example 7 is shown.
[0047] Figure 8 Anodic linear sweep voltammetry performed on the polymer electrolyte of Example 8 is shown.
[0048] Fig. 9 Shown is the EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Example 1 (impedance after each 6 hours of rest).
[0049] Fig.10 The EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Example 2 is shown (impedance after each 6 hours of rest).
[0050] Fig.11 The EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Example 3 is shown (impedance after each 6 hours of rest).
[0051] Fig.12 EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Example 4 is shown (impedance after each 6 hours of rest).
[0052] Fig.13 The EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Comparative Example 5 is shown (impedance after each 6 hours of rest).
[0053] Fig.14 The EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Comparative Example 6 is shown (impedance after each 6-hour rest).
[0054] Fig.15 The EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Example 7 is shown (impedance after each 6 hours of rest).
[0055] Fig.16 The EIS characterization of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Example 8 is shown (impedance after each 6 hours of rest).
[0056] Fig.17 The cycling capacities of cells including NMC622 and Li electrodes and Example 1 and Example 2 electrolytes are shown. The discharge capacities are the average of three cells at each C rate. The capacities are normalized to the mass of active material in the positive electrode.
[0057] Fig.18 The cycling capacities of cells including NMC622 and Li electrodes and Example 3 and Example 4 electrolytes are shown. The discharge capacity is the average of three cells at each C rate. The capacity is normalized to the mass of active material in the positive electrode.
[0058] Fig.19 The cycling capacities of cells including NMC622 and Li electrodes and electrolytes of Comparative Example 5 and Comparative Example 6 are shown. The discharge capacity is the average of three cells at each C rate. The capacity is normalized to the mass of active material in the positive electrode.
[0059] Fig. 20 The cycling capacities of cells including NMC622 and Li electrodes and Example 7 and Example 8 electrolytes are shown. The discharge capacity is the average of three cells at each C rate. The capacity is normalized to the mass of active material in the positive electrode.
[0060] Fig.21 Shown is the EIS characterization (impedance after every 6 hours) of a symmetric cell comprising an NMC622 electrode impregnated with the polymer electrolyte of Example 9 and the polymer electrolyte of Example 9.
[0061] Fig. 22 EIS characterization (impedance after every 6 hours) of a symmetric cell comprising NMC622 electrodes and the polymer electrolyte of Comparative Example 10 is shown. DETAILED DESCRIPTION
[0062] In the following specific embodiments, preferred embodiments are described in detail to practice the present invention. Although the present invention is described with reference to these specific preferred embodiments, it should be understood that the present invention is not limited to these preferred embodiments. On the contrary, the present invention includes many substitutions, modifications and equivalent forms, which will become apparent by considering the following specific embodiments.
[0063] As used herein, the expression "comprise" and its variations (such as "comprises / comprising") should be interpreted in an open, inclusive sense, meaning that the described embodiments include the recited features, and it does not exclude the presence of other features as long as they do not render the embodiment inoperable.
[0064] As used herein, the expressions "one embodiment," "particular embodiment," "embodiment," and the like should be interpreted as meaning that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, the appearances of such expressions in various places in this specification are not necessarily all referring to the same embodiment. Furthermore, the specific features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. For example, certain features of the present disclosure described herein in the context of separate embodiments are also expressly contemplated to be combined in a single embodiment.
[0065] As used herein, the singular forms "a", "an", "the", and "said" should be construed to include plural referents, unless the context clearly dictates otherwise. It should also be noted that the term "or" is generally used in its broadest sense, i.e., as in the sense of "and / or", unless the context clearly dictates otherwise.
[0066] As used herein, the expression "cathode active material" may also be interchangeably referred to as "positive electrode active material". As will be appreciated by those skilled in the art, the cathode polarity may be positive or negative, depending on the mode of operation of the electrochemical cell containing the cathode active material. The term "cathode active material" or "positive electrode active material" as used herein and in the claims is defined as a material that is electrochemically active in the positive electrode or cathode. By active material, it must be understood that the material is capable of capturing and releasing lithium ions when subjected to a voltage change over a predetermined period of time.
[0067] As used herein, the expression "(meth)acrylamide" should be interpreted as "methacrylamide, acrylamide, or a combination thereof." For example, N-dialkyl(meth)acrylamide should be interpreted as "N-dialkylmethacrylamide, N-dialkylacrylamide, or a combination thereof."
[0068] In the context of the present disclosure, when it is noted that a substituent (optionally) comprises a certain number of functional groups (e.g. one or two) functional groups, this should be interpreted as meaning that the substituent has exactly the stated number of functional groups. For example, the expression "selected from C1-C6 hydroxyalkyl, wherein the C1-C6 hydroxyalkyl comprises one hydroxyl functional group" should be interpreted as meaning that there is exactly one (1) hydroxyl functional group.
[0069] The parameters x, y, z and a as mentioned herein in the context of the composition of the cathode active material are measured by Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES).
[0070] Ionic conductivity as referred to herein refers to the ionic conductivity measured by electrochemical impedance spectroscopy (EIS) (using Biologic SP-300) in a symmetrical stainless steel|electrolyte|stainless steel Swagelok type cell at the specified temperature by perturbing the open circuit potential with an AC sinusoidal potential of 10 mV amplitude in the frequency range of 10 kHz-100 mHz.
[0071] The "anodic stability limit" as referred to herein is determined by linear sweep voltammetry (preferably using a Bio-Logic, SP-300) of a polymer electrolyte sandwiched between a stainless steel working electrode, a lithium metal reference electrode and a counter electrode in a button cell setup, wherein the voltage at the working electrode is swept from the open circuit potential to 6 V vsLi in the anodic scan. + / Li, scan rate 10mV s -1 The stability limit was determined as the onset of electrolyte oxidation, which can be observed by a sudden increase in the measured current.
[0072] Composite cathode of the present invention
[0073] In a first aspect of the present invention, there is provided a composite cathode comprising a cathode active material and a polymer electrolyte, wherein the cathode active material comprises Li, M and O, wherein M comprises Ni and comprises one or both of Mn and Co, wherein the polymer electrolyte comprises an electrolyte composition and a polymer network, wherein the electrolyte composition preferably comprises a deep eutectic solvent (DES), wherein the polymer electrolyte is obtainable by polymerizing a precursor composition comprising the electrolyte composition and a first monomer according to formula (I)
[0074]
[0075] in
[0076] R 1 represents a first substituent having 1 to 8 carbon atoms and optionally comprising at least one functional group selected from alcohol, amine, ether, ketone, amide, acetal, ketal, aminoacetal, hemiaminal ether or a combination thereof, preferably wherein R 1 Selected from C1-C6 alkyl, C1-C6 hydroxyalkyl, -(CH2-CH2-O) n -H;
[0077] and
[0078] Where R 2 represents H or a second substituent having 1 to 8 carbon atoms and optionally comprising at least one functional group selected from alcohol, amine, ether, ketone, amide, acetal, ketal, aminoacetal, hemiaminal ether or a combination thereof, preferably wherein R 2Selected from H, C1-C6 alkyl, C1-C6 hydroxyalkyl, -(CH2-CH2-O) n -H;
[0079] Where R 3 is selected from H, methyl or ethyl; and
[0080] wherein n is an integer from 1 to 5.
[0081] In some embodiments of the present invention, there is provided a composite cathode as described herein, with the proviso that the monomer according to formula (I) is not N,N-dimethylacrylamide.
[0082] The polymer network mentioned in the present disclosure is a three-dimensional network, which can be obtained by polymerization of one or more monomers according to formula (I) in the presence of a crosslinking agent. Such three-dimensional polymer networks are also referred to as gels, so that the polymer electrolytes described in the context of the present invention can also be referred to as "gel polymer electrolytes". For the purposes of the present disclosure, a gel polymer refers to a polymer network (i.e., a three-dimensional crosslinked system) that does not exhibit flow when in a steady state but allows a liquid phase to diffuse through the polymer network. Preferably, the gel is self-supporting. Such gels generally exhibit a combination of flexibility, mechanical robustness, low vapor pressure, and preferably non-flammability.
[0083] As will be understood by those skilled in the art based on this disclosure, the electrolyte composition comprises a polymer network. The electrolyte composition is typically confined in the polymer network, which means that when the polymer electrolyte of the present invention is placed on a surface (e.g., a ceramic laboratory bench) without applying external pressure, substantially no electrolyte composition spontaneously flows out of the polymer electrolyte. In all aspects of the present invention, it is highly preferred that the electrolyte composition is liquid at 20°C in the absence of a polymer network.
[0084] In a preferred embodiment of the present invention, there is provided a cathode composite material according to the present invention, wherein the first monomer is selected from compounds according to formula (I)
[0085] Where R 1 represents a first substituent having 1 to 6 carbon atoms and optionally comprising one or two functional groups selected from alcohol, amine, ether, ketone, amide, acetal, ketal, aminoacetal, hemiaminal ether or a combination thereof;
[0086] Where R 2 represents H or a second substituent having 1 to 6 carbon atoms and optionally comprising one or two functional groups selected from alcohols, amines, ethers, ketones, amides, acetals, ketals, aminoacetals, hemiaminal ethers or combinations thereof, preferably wherein R 2 Selected from H, C1-C6 alkyl, C1-C6 hydroxyalkyl, -(CH2-CH2-O) n-H;
[0087] Where R 3 is selected from H, methyl or ethyl; and
[0088] wherein n is an integer from 1 to 5.
[0089] In a more preferred embodiment of the present invention, there is provided a cathode composite material of the present invention, wherein the first monomer is selected from compounds according to formula (I)
[0090] Where R 1 represents a first substituent having 1 to 6 carbon atoms and optionally comprising one or two functional groups selected from alcohols;
[0091] Where R 2 represents H or a second substituent having 1 to 6 carbon atoms and optionally comprising one or two functional groups selected from alcohols, preferably wherein R 2 is selected from H, C1-C6 alkyl, C1-C6 hydroxyalkyl, wherein the C1-C6 hydroxyalkyl contains a hydroxyl functional group;
[0092] Where R 3 is selected from H, methyl or ethyl; and
[0093] wherein n is an integer from 1 to 5.
[0094] In a highly preferred embodiment of the present invention, a cathode composite material is provided wherein the first monomer is according to option A, B or C:
[0095] AR 1 Selected from C1-C6 alkyl, preferably R 1 is a C3 alkyl group, and R 2 Selected from H or methyl, preferably R 2 is H, and R 3 Selected from H or methyl, preferably R 3 is H; or
[0096] BR 1 Selected from C1-C6 alkyl, preferably R 1 is a C2 alkyl group, and R 2 Selected from C1-C6 alkyl, preferably R 2 is a C2 alkyl group, and R 3 Selected from H or methyl, preferably R 3 is H; or
[0097] CR 1 is selected from C1-C6 hydroxyalkyl, wherein the C1-C6 hydroxyalkyl contains a hydroxyl functional group, preferably R 1 is 2-hydroxyethyl, R 2 Selected from H or methyl, preferably R 2is H, and R 3 Selected from H or methyl, preferably R 3 It's H.
[0098] In some embodiments of the present invention, a cathode composite is provided wherein the first monomer is according to Option B, with the proviso that the first monomer is not N,N-dimethylacrylamide.
[0099] In a preferred embodiment of the present invention, a cathode composite material is provided, wherein the first monomer according to formula (I) is selected from N-isopropylacrylamide (NIPAM), N,N-diethylacrylamide (DEAA), N-(2-hydroxyethyl)acrylamide (HEAA) and combinations thereof.
[0100] In a preferred embodiment of the invention, the first monomer comprises at least 80 mol%, preferably at least 90 mol%, more preferably at least 95 mol% of all monomers in the precursor composition of the polymer network of the electrochemical cell. In a highly preferred embodiment of the invention, the first monomer comprises at least 98 mol%, 99 mol% or about 100 mol% of all monomers in the composition. For the purpose of determining the total amount of monomers in the precursor composition, any compound that can polymerize with the first monomer and has a functionality of 1 is considered a monomer, wherein the functionality is determined based on the functional groups that can free radically polymerize with the acrylamide functionality of the first monomer.
[0101] The composite cathode of the present invention can be provided in various forms. In some embodiments of the present invention, the composite cathode comprises a homogeneous mixture of cathode active material particles and polymer electrolyte particles. The homogeneous mixture may contain additional ingredients. In a preferred embodiment of the present invention, the cathode active material is porous, and the polymer electrolyte is coated on the cathode active material and / or at least partially embedded in the cathode active material. Such coated or embedded materials can be obtained by contacting a precursor composition with the cathode active material and by polymerizing the precursor composition in the presence of the cathode active material. This is explained in more detail elsewhere herein.
[0102] Crosslinking agent
[0103] According to a preferred embodiment of the present invention, the precursor composition further comprises a first crosslinking agent. Since the first monomer is monofunctional (it is a (meth)acrylamide according to formula (I)), the inclusion of a crosslinking agent in the precursor composition allows the formation of a three-dimensional polymer network. The crosslinking agent can be selected from any compound that can polymerize with the first monomer and has a functionality of 2 or more, wherein the functionality is determined based on the functional group that can free radically polymerize with the acrylamide functionality of the first monomer.
[0104] Preferably, the first crosslinking agent is selected from a crosslinking agent comprising two or more functional groups selected from the group consisting of allyl (-CH3-CH=CH2), oxirane (-C2H3O), glycidyl (-CH2-C2H3O), vinyl ether (-O-CH=CH2), vinyl ester (-C(O)-O-CH=CH2), vinyl amide (-C(O)-NH-CH=CH2), vinyl amine (-NH-CH=CH2), norbornene, maleate, fumarate, itaconate, alkynyl (-C≡CH), styrene (-Ph-CH=CH2), acrylamide (-NH-C(O)-CH =CH2), methacrylamide (-NH-C(O)-C(CH3)=CH2), acrylate (-OC(O)-CH=CH2), methacrylate (-OC(O)-C(CH3)=CH2) and combinations thereof, preferably the first crosslinking agent is selected from a crosslinking agent comprising two or more functional groups selected from the group consisting of acrylamide (-NH-C(O)-CH=CH2), methacrylamide (-NH-C(O)-C(CH3)=CH2), acrylate (-OC(O)-CH=CH2), methacrylate (-OC(O)-C(CH3)=CH2) and combinations thereof. In some embodiments of the present invention, the first crosslinking agent comprises two, three or four functional groups selected from the functional groups described in the preceding sentence, however, it is preferred if the first crosslinking agent comprises two identical or different functional groups selected from the functional groups described in the preceding sentence.
[0105] Examples of suitable and therefore preferred embodiments of the first crosslinking agent are those wherein the first crosslinking agent is selected from the group consisting of allyl methacrylate, allyl acrylate, glycidyl methacrylate, ethylene glycol dicyclopentyl ether methacrylate, ethylene glycol dicyclopentyl ether acrylate, triethylene glycol divinyl ether, poly(ethylene glycol) diacrylamide, poly(ethylene glycol) dimethacrylate, poly(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol divinyl ether, Acrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, tetraethylene glycol diacrylate, propylene glycol dimethacrylate, propylene glycol diacrylate, 1,4-butanediol dimethacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol dimethacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol dimethacrylate, 1,6-hexanediol diacrylate, 1,10-bis(acryloyloxy)decane, 1,12-dodecane dimethacrylate, alcohol dimethacrylate, 1,12-dodecanediol diacrylate, poly(silicone-alt-PEG) dimethacrylate, poly(silicone-alt-PEG) diacrylate, poly(propylene glycol) dimethacrylate, poly(propylene glycol) diacrylate, bisphenol A propoxylated dimethacrylate, bisphenol A propoxylated diacrylate, neopentyl glycol propoxylated dimethacrylate, neopentyl glycol propoxylated diacrylate, glycerol ethoxylate-co-propoxylated dimethacrylate, glycerol ethoxylated Propylene glycol dimethacrylate, propylene glycol diacrylate, polycaprolactone dimethacrylate, polycaprolactone diacrylate, pentaerythritol propoxylated dimethacrylate, pentaerythritol propoxylated diacrylate, tri(propylene glycol) dimethacrylate, tri(propylene glycol) diacrylate, diurethane dimethacrylate (DUDMA), 1,3,5-triallyl-2,4,6(1H,3H,5H)-trione, 2,4,6,-triallyloxy-1,3,5, triazine, trimethylolpropane propoxylate trimethacrylate, trimethylolpropane propoxylate triacrylate, glycerol propoxylated trimethacrylate, glycerol propoxylated triacrylate, polycaprolactone trimethacrylate (PCLTMA), polycaprolactone triacrylate, tri-(4-hydroxyphenyl)ethane trimethacrylate, tri-(4-hydroxyphenyl)ethane triacrylate, trimethylolpropane ethoxylate trimethacrylate, trimethylolpropane ethoxylate triacrylate, glycerol ethoxylate trimethacrylate, glycerol ethoxylate triacrylate, pentaerythritol ethoxylate trimethacrylate, pentaerythritol ethoxylated triacrylate, ethylenediaminetetra(ethoxylated-block-propoxylate)tetramethacrylate, ethylenediaminetetra(ethoxylated-block-propoxylate)tetraacrylate and pentaerythritol propoxylate tetramethacrylate, pentaerythritol propoxylate tetraacrylate, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, N,N'-ethylenebisacrylamide, N,N'-ethylenebismethacrylamide, N,N'-propylenebisacrylamide, N,N'-propylenebismethacrylamide, N,N'-butylenebisacrylamide, N,N'-butylenebismethacrylamide, N,N'-pentylenebisacrylamide, N,N'-pentylenebismethacrylamide, N,N'-hexylenebisacrylamide, N,N'-hexylenebismethacrylamide, N,N'-heptylenebisacrylamide, N,N'-heptylenebismethacrylamide, N,N'-octylenebisacrylamide, N,N'-octylenebismethacrylamide, and combinations thereof. In a preferred embodiment of the present invention, the first crosslinking agent is selected from the group consisting of poly(ethylene glycol) dimethacrylate, poly(ethylene glycol) diacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, tetraethylene glycol diacrylate, propylene glycol dimethacrylate, propylene glycol diacrylate, 1,4-butanediol dimethacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol dimethacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol dimeth ...acrylate, 1,6-hexanediol dimethacrylate, propylene glycol dimethacrylate, propylene glycol diacrylate, 1,4-butanediol dimethacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol dimethacrylate, propylene glycol dimethacrylate, propylene glycol diacrylate, 1,4-butane acrylate, 1,6-hexanediol diacrylate, 1,10-bis(acryloyloxy)decane, 1,12-dodecanediol dimethacrylate, 1,12-dodecanediol diacrylate, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, N,N'-ethylenebisacrylamide, N,N'-ethylenebismethacrylamide, N,N'-propylenebisacrylamide, N,N'-propylenebismethacrylamide, N,N'-butylenebisacrylamide, N,N'-butylenebismethacrylamide, N,N'-pentylenebisacrylamide, N,N'-pentylenebismethacrylamide, N,N'-hexylenebisacrylamide, N,N'-hexylenebismethacrylamide, N,N'-heptylenebisacrylamide, N,N'-heptylenebismethacrylamide, N,N'-octylenebisacrylamide, N,N'-octylenebismethacrylamide and combinations thereof. In a highly preferred embodiment of the present invention, the first crosslinking agent is selected from ethylene glycol dimethacrylate, ethylene glycol diacrylate, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide and combinations thereof.
[0106] In some embodiments of the present invention, the first cross-linking agent is selected from a compound according to formula (IIa), a compound according to formula (IIb), or a combination thereof.
[0107]
[0108]
[0109] Where R 4 , R 5 , R 6 and R 7 are each independently selected from H, methyl or ethyl,
[0110] Where R 8 and R 9 are each independently selected from H or methyl,
[0111] Wherein X is an alkanediyl or polyoxyalkylene group, preferably X is (-CH2-) m or -CH2-CH2(-O-CH2-CH2) o -,
[0112] Wherein Y is an alkanediyl or polyoxyalkylene group, preferably Y is (-CH2-) n or -CH2-CH2(-O-CH2-CH2) p -,
[0113] Where m is an integer in the range of 1-10,
[0114] Where n is an integer in the range 1-10,
[0115] Where o is an integer in the range of 1-200,
[0116] Where p is an integer in the range of 1-200.
[0117] As shown in the accompanying examples, these cross-linking agents were found to have excellent compatibility with the first monomer and resulted in polymer electrolytes with desirable electrochemical and mechanical properties.
[0118] In a preferred embodiment of the present invention, X is selected from (-CH2-)m , wherein m is in the range of 1 to 6, preferably in the range of 1 to 4, and more preferably m is equal to 2.
[0119] In a preferred embodiment of the present invention, Y is selected from (-CH2-) n , wherein n is in the range of 1 to 6, preferably in the range of 1 to 4, and more preferably n is equal to 1.
[0120] As will be appreciated by those skilled in the art, when X is -CH2-CH2 (-O-CH2-CH2) o - or Y is -CH2-CH2(-O-CH2-CH2) p -, the compound of formula (IIa) or (IIb) will in practice be provided in the form of a mixture of compounds having different degrees of ethoxylation and therefore different values of o and p. Preferably, in the case where the precursor composition comprises one or more crosslinking agents according to formula (IIa), wherein X is -CH2-CH2 (-O-CH2-CH2) o -, the number average o determined for all compounds of formula (IIa) in the precursor composition is in the range of 1-200, preferably in the range of 2-20. Similarly, it is preferred that in the case where the precursor composition comprises one or more crosslinking agents according to formula (IIb), wherein Y is -CH2-CH2 (-O-CH2-CH2) p -, the number average p determined for all compounds of the formula (IIb) in the precursor composition is in the range of 1-200, preferably in the range of 2-20.
[0121] The precursor composition may typically include additional additional crosslinking agents in addition to the first crosslinking agent. However, in some preferred embodiments of the present invention, the first crosslinking agent is the only crosslinking agent present. Generally, it is preferred that the average functionality determined for all crosslinking agents in the precursor composition is in the range of 2-3, preferably in the range of 2-2.5, and most preferably in the range of 2-2.2. For the purpose of determining this average functionality, any compound that can polymerize with the first monomer and has a functionality of 2 or more is considered a crosslinking agent, wherein the functionality is determined based on the functional groups that can free radically polymerize with the acrylamide functionality of the first monomer.
[0122] As will be appreciated by those skilled in the art, the amount of crosslinking agent used in the precursor composition will affect the mechanical properties as well as the electrochemical properties of the polymer electrolyte obtained. In a preferred embodiment of the present invention, the first crosslinking agent is contained in the precursor composition in an amount such that the molar ratio of the total amount of the first monomer contained in the precursor composition to the total amount of the first crosslinking agent contained in the precursor composition is in the range of 99.5:0.5 to 80:20, preferably in the range of 98:2 to 80:20, and more preferably in the range of 95:5 to 85:15. In the case where the precursor composition contains an additional additional crosslinking agent in addition to the first crosslinking agent, it is preferred that the total amount of crosslinking agent in the precursor composition is in the range of 99.5:0.5 to 80:20, preferably in the range of 98:2 to 80:20, and more preferably in the range of 95:5 to 85:15. For the purpose of determining the total amount of crosslinking agent, any compound that can be polymerized with the first monomer and has a functionality of 2 or more is considered a crosslinking agent, wherein the functionality is determined based on the functional group that can be free-radical polymerized with the acrylamide functionality of the first monomer.
[0123] According to a preferred embodiment of the present invention, the precursor composition further comprises one or more free radical initiators, preferably one or more free radical initiators selected from thermal initiators, photoinitiators and combinations thereof.
[0124] Suitable thermal free radical initiators include, but are not limited to, benzoyl peroxide, dibenzoyl peroxide, succinic acid peroxide, dilauroyl peroxide, didecanoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, di-tert-amyl peroxide, α,α'-di(tert-butylperoxy)diisopropyl-benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, tert-butylperoxide, α-cumyl peroxyneodecanoate, α-cumyl peroxyneoheptanoate, tert-amyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, di-(2-ethylhexyl)dicarbonate, tert-Amyl peroxypivalate, tert-Butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, dibenzoyl peroxide, tert-Amyl peroxy-2-ethylhexanoate, tert-Butyl peroxy-2-ethylhexanoate, 1,1-di-(tert-Amyl peroxy)cyclohexane, 1,1-di(tert-Butyl peroxy)3,3,5-trimethylcyclohexane, 1,1-di-(tert-Butyl peroxy)cyclohexane, OO-tert-Amyl-O(2-ethylhexyl)monoperoxycarbonate, OO-tert-Butyl O-isopropyl monoperoxycarbonate, OO-tert-Butyl O-(2-ethylhexyl)monoperoxycarbonate, peroxy tert-amyl benzoate, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, ethyl 3,3-di(tert-amylperoxy)butyrate, ethyl 3,3-di(tert-butylperoxy)butyrate, dicumyl peroxide; and azo compounds such as 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexanenitrile), azobisisobutyronitrile (AIBN) and 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane disulfate dihydrate, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamide] hydrate, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(1-imino-1-pyrrolidone-2-ethylpropane) dihydrochloride, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], cumene hydroperoxide and ammonium persulfate.
[0125] Suitable free radical photoinitiators include, but are not limited to, benzophenone (e.g., "IRGACURE 500"), 3-methylbenzophenone, 2-methylbenzophenone, 3,4-dimethylbenzophenone, 3-hydroxybenzophenone, 4-hydroxybenzophenone, 4,4'-dihydroxybenzophenone, 4-benzoylbenzoic acid, 2-benzoylbenzoic acid, 2-benzoylbenzoic acid methyl ester, 4,4'-carbonyldiphthalic anhydride, methylbenzoylformate (e.g., "DAROCUR MBF"), 1-hydroxy-cyclohexyl-phenyl-ketone (e.g., "IRGACURE 184"), 2-hydroxy-2-methyl-1-phenyl-1-propanone (e.g., "DAROCUR 1173"), 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (e.g., "IRGACURE 2959"), 2-[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl oxy-phenyl-acetate and 2-[2-hydroxy-ethoxy]-ethyl oxy-phenyl-acetate (e.g., "IRGACURE 754"), α,α-dimethoxy-α-phenylacetophenone (also known as 2,2-dimethoxy-2-phenyl-acetophenone (DMPA) (e.g., "IRGACURE 651"), 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone (e.g., "IRGACURE 369"), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone (e.g., "IRGACURE 907"), biphenyl(2,4,6-trimethylbenzyl)-phosphine oxide (e.g., "DAROCURTPO"), phosphine oxide, phenylbis(2,4,6-trimethylbenzoyl) (e.g., "IRGACURE 819"), bis(η5-2,4-cyclopentadien-1-yl)bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium (e.g., "IRGACURE 784"), 1-hydroxy-cyclohexyl-phenyl-ketone (e.g., "IRGACURE 184"), 2-hydroxy-2-methyl-1-phenyl-1-propanone (e.g., "DAROCUR 1173"), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one (e.g., "IRGACURE 127”), 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (e.g., “IRGACURE 2959”), phenylglyoxylate, oxy-phenyl-acetic acid 2-[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl ester, oxy-phenyl-acetic acid 2-[2-hydroxy-ethoxy]-ethyl ester, phenylglyoxylic acid methyl ester (e.g., “DAROCUR MBF”), 2,4,6-trimethylol-biphenylphosphine oxide (e.g., "LUCIRIN TPO"), 2,4,6-trimethylol-biphenylphosphine salt (e.g., "LUCIRIN TPO-L"), liquid blends of acylphosphine oxides (e.g., "IRGACURE 2100"), bis(2,4,6-trimethylol)-phenylphosphine oxide (e.g., "IRGACURE 819"), titanocene, bis(η5-2,4-cyclopentadien-1-yl)bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl] (e.g., "IRGACURE 784"), [1-(4-phenylthiobenzoyl)heptyleneamino]benzoate (e.g., "IRGACURE OXE 01")), [1-[9-ethyl-6-(2-methylbenzoyl)carbazol-3-yl]ethylideneamino]acetate (e.g., "IRGACURE OXE 02"), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (e.g., "IRGACURE 907"), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one (e.g., "IRGACURE 369"), 2-dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one (e.g., "IRGACURE 379"), benzyl dimethyl ketal, 2,2-dimethoxy-1,2-biphenylethyl-1-one (e.g., "IRGACURE 651”), camphorquinone, acetophenone, 4'-hydroxyacetophenone, 3'-hydroxyacetophenone, 4-(dimethylamino)-benzophenone, 4,4'-bis(dimethylamino)-benzophenone, 4,4'-bis(diethylamino)-benzophenone, 4,4'-dichlorobenzophenone, 4-phenylbenzophenone, 1,4-dibenzoylbenzene, 4-(p-tolylthio)-benzophenone, dibenzosuberenone, benzil, p-anisil, methyl benzoylformate, 9,10-phenanthrenequinone, 2-benzoyl-2-propanol, 2-hydroxy-4'-(2-hydroxyethoxy) -2-methylpropiophenone, 1-methylpropiophenone, benzoin, anisoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-diethoxyacetophenone, benzyl dimethyl ketal, 2-methyl-4'-(methylthio)-2-morpholinoacetophenone, 2-benzyl-2-(dimethylamino)-4'-morpholinobutanedione, 2-isonitrosopropiophenone, 9,10-phenanthrenequinone, 2-ethylanthraquinone, anthraquinone-2-sulfonate sodium, 2-chlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-isopropylthioxanthone, 2,4-diethylthioxanthene-9-one, 2,7-dimethoxythioxanthone, 2,2'-Bis(2-chlorophenyl)4,4',5,5'-tetraphenyl-1,2'-biimidazole, biphenyl(2,4,6-trimethyl-benzoyl)phosphine oxide, phenylbis(2,4,6-trimethyl-benzoyl)phosphine oxide, lithium phenyl-(2,4,6-trimethylbenzoyl)phosphinate and ferrocene.
[0126] In some embodiments of the present invention, the precursor composition further comprises one or more free radical initiators selected from 2,2-dimethoxy-2-phenyl-acetophenone (DMPA), azobisisobutyronitrile (AIBN), and combinations thereof.
[0127] The one or more free radical initiators are preferably used in an amount such that the molar ratio of the total amount of the first monomer contained in the precursor composition to the total amount of the one or more free radical initiators contained in the precursor composition is in the range of 99.8:0.2 to 80:20, preferably in the range of 99:1 to 85:15, and more preferably in the range of 98:2 to 90:10.
[0128] Electrolyte composition
[0129] As will be appreciated by those skilled in the art, in order to obtain a gel-type polymer electrolyte, it is preferred that the polymer is synthesized in the presence of an electrolyte composition, thereby effectively encapsulating the electrolyte composition in the polymer network. However, without wishing to be bound by any theory, other methods of obtaining a polymer electrolyte as described herein are also feasible, such as exchanging another liquid composition (e.g., a solvent) encapsulated in a polymer for an electrolyte composition, absorbing the electrolyte composition into a preformed polymer network, injecting the electrolyte composition into a preformed polymer network, etc. Therefore, according to the present invention, the polymer electrolyte contained in the composite cathode can be obtained by polymerizing a precursor composition comprising an electrolyte composition and other components (monomers, crosslinkers, initiators, etc.) as discussed throughout this disclosure. In all aspects of the present invention, it is highly preferred that the electrolyte composition is liquid at 20°C in the absence of a polymer network.
[0130] As shown in the accompanying examples, the inventors have found that polymer electrolytes loaded with deep eutectic solvents (DES) exhibit excellent performance, especially when combined with high potential cathode active materials (such as NMC622). Therefore, according to a highly preferred embodiment of the present invention, the electrolyte composition comprises or consists of a deep eutectic solvent (DES). The deep eutectic solvent is preferably liquid at 20°C.
[0131] It has been found that different relative amounts of DES and polymer produce functional electrolyte materials. The precursor composition preferably comprises about 45% to 95% by volume (based on the total volume of the precursor composition) of a deep eutectic solvent (DES), preferably about 55% to 90% by volume, more preferably 70% to 90% by volume. It was found that a precursor composition with about 85% by volume of DES provides excellent ionic conductivity and mechanical properties (increased flexibility). Therefore, in a highly preferred embodiment of the present invention, the precursor composition comprises about 75% to 90% by volume (based on the total volume of the precursor composition) of a deep eutectic solvent (DES), preferably about 80% to 90% by volume, most preferably about 83% to 87% by volume. The remainder of the precursor composition consists of a first monomer (optionally additional monomers), a first crosslinking agent (optionally additional crosslinking agents), one or more free radical initiators, and optional additional components. In some embodiments, the remainder of the precursor composition consists essentially of a first monomer (optionally additional monomers), a first crosslinking agent (optionally additional crosslinking agents), and one or more free radical initiators.
[0132] The deep eutectic solvent (DES) preferably has a eutectic point of less than or equal to 25°C, preferably a eutectic point equal to or less than 15°C, more preferably less than or equal to 0°C. In a highly preferred embodiment of the present invention, the deep eutectic solvent (DES) has a eutectic point less than or equal to -15°C, most preferably less than or equal to -25°C. This allows the DES to remain liquid within the typical operating temperature window of electrochemical cells for conventional applications (such as automobiles). The eutectic point referred to herein is determined at a pressure of about 101 kPa.
[0133] The deep eutectic solvent (DES) preferably comprises at least one hydrogen bond acceptor and at least one hydrogen bond donor. The molar ratio of hydrogen bond acceptor to hydrogen bond donor is preferably at least 1:1, more preferably at least 1:2, more preferably at least 1:3. In a preferred embodiment of the present invention, the electrolyte composition comprises or consists of (preferably consists of) a deep eutectic solvent (DES) containing at least one hydrogen bond acceptor and at least one hydrogen bond donor, wherein the molar ratio of hydrogen bond acceptor to hydrogen bond donor is in the range of 1:1 to 1:8, preferably in the range of 1:2 to 1:6, more preferably in the range of 1:3 to 1:5. A highly preferred molar ratio of hydrogen bond acceptor to hydrogen bond donor (particularly in the case where the hydrogen bond acceptor is lithium bis(trifluoromethanesulfonyl)imide as described elsewhere herein and / or in the case where the hydrogen bond donor is N-methylacetamide as described elsewhere herein) is in the range of 1:3.5 to 1:4.5, such as about 1:4.
[0134] In a preferred embodiment of the present invention, the hydrogen bond acceptor comprises a lithium salt, a zinc salt or a combination thereof, preferably a lithium salt. In a more preferred embodiment, the hydrogen bond acceptor is selected from the group consisting of: lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium chloride (LiCl), lithium hexafluorophosphate (LiPF6), lithium polysulfide, lithium perchlorate (LiClO4), lithium bromide (LiBr), lithium iodide (LiI), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(oxalate)borate (LiBOB), lithium fluoroalkyl phosphate (LFAP), lithium fluoride (LiF ... [LiPF3(CF2CF3)3]) and combinations thereof, preferably lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and / or a hydrogen bond donor selected from the group consisting of urea, N-methylurea, N,N-dimethylurea, N,N'-dimethylurea, N,N,N'-trimethylurea, thiourea, N-methylthiourea, N,N-dimethylthiourea, N,N'-dimethylthiourea, N,N,N'-trimethylthiourea, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4 -butanediol, 1,2,3-propanetriol, acetic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, benzoic acid, glycolic acid, citric acid, 2-hydroxypropionic acid, 2-hydroxyisobutyric acid, o-phenylenediamine, choline chloride, acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, benzamide, benzenesulfonic acid, p-toluenesulfonic acid, o-toluenesulfonic acid, m-toluenesulfonic acid and combinations thereof, preferably N-methylacetamide.
[0135] Therefore, in some embodiments of the present invention, the electrolyte composition consists of a deep eutectic solvent (DES) comprising, preferably consisting of, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and N-methylacetamide, wherein the molar ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to N-methylacetamide is in the range of 1:1 to 1:8, preferably in the range of 1:2 to 1:6, more preferably in the range of 1:3 to 1:5, such as about 1:4.
[0136] The electrolyte composition preferably comprises at least 90 wt % (by the total weight of the electrolyte composition), preferably at least 95 wt %, more preferably at least 99 wt % DES. In some embodiments, the electrolyte composition comprises water, such as 0.1 wt %-30 wt % (by the total weight of the electrolyte composition) of water, or 0.1 wt %-10 wt % (by the total weight of the electrolyte composition) of water. In other preferred embodiments, the electrolyte composition comprises less than 5 wt % of water, preferably less than 0.1 wt % of water, more preferably less than 0.01 wt % of water. In some embodiments, the electrolyte composition is substantially free of water. The latter is particularly preferably used in combination with moisture sensitive electrodes such as Li or graphite. In all embodiments described herein, the electrolyte composition is preferably composed of a deep eutectic solvent (DES).
[0137] As will be understood by those skilled in the art in the context of the present disclosure, the precursor composition consists essentially of an electrolyte composition as described herein in combination with a first monomer, a first crosslinker, and one or more initiators as described herein. Thus, according to a preferred embodiment of the present invention, the precursor composition comprises at least 90% by weight (based on the total weight of the precursor composition) of the combined amount of the electrolyte composition, the first monomer (optionally additional monomers), the first crosslinker (optionally additional crosslinkers), and the one or more free radical initiators, preferably at least 95% by weight (based on the total weight of the precursor composition), and more preferably at least 99% by weight (based on the total weight of the precursor composition). In some embodiments, the precursor composition comprises at least 90% by weight (based on the total weight of the precursor composition) of the combined amount of the electrolyte composition, the first monomer, the first crosslinker, and the one or more free radical initiators, preferably at least 95% by weight (based on the total weight of the precursor composition), and more preferably at least 99% by weight (based on the total weight of the precursor composition). As explained previously herein, any compound that is polymerizable with the first monomer and has a functionality of 1 is considered a monomer, and any compound that is polymerizable with the first monomer and has a functionality of 2 or more is considered a crosslinker, wherein the functionality is determined based on the functional groups that are free radically polymerizable with the acrylamide functionality of the first monomer. Thus, according to a preferred embodiment of the present invention, the polymer electrolyte comprises at least 90% by weight (based on the total weight of the polymer electrolyte) of the combined weight of the polymer network and the electrolyte composition, more preferably at least 98% by weight (based on the total weight of the polymer electrolyte), and most preferably at least 99% by weight (based on the total weight of the polymer electrolyte). In some embodiments, the polymer electrolyte consists essentially of the polymer network and the electrolyte composition.
[0138] In a preferred embodiment of the present invention, a composite cathode of the present invention is provided wherein the polymer electrolyte has a voltage of at least 4.6 V vs Li + / Li, preferably at least 4.7V vs Li + / Li anode stability limit.
[0139] Cathode active material
[0140] As shown in the accompanying examples, the inventors have found that the polymer electrolyte used in the composite cathode of the present invention exhibits surprisingly good electrochemical performance when used in combination with a high potential cathode active material. Thus, the cathode active material preferably has a potential of at least 4.3 V vs. Li + / Li, preferably at least 4.4V vs.Li + / Li, more preferably at least 4.5V vs.Li + / Li upper cut-off voltage.
[0141] The cathode active material is preferably a cathode active material comprising Li, M and O, wherein M comprises:
[0142] - Nickel content x, where 50.0 mol % ≤ x ≤ 95.0 mol %, preferably where 55.0 mol % ≤ x ≤ 95.0 mol %,
[0143] - Mn with a content of y, where 0.0mol%≤y≤40.0mol%,
[0144] -Co with content z, where 0.0mol%≤z≤40.0mol%,
[0145] - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O,
[0146] - wherein x+y+z+a is 100.0 mol%;
[0147] Preferably wherein M comprises:
[0148] -Ni with content x, where 50.0mol%≤x≤85.0mol%,
[0149] - Mn with a content of y, where 7.5mol%≤y≤25.0mol%,
[0150] -Co with content z, where 7.5mol%≤z≤25.0mol%,
[0151] - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O,
[0152] - wherein x+y+z+a is 100.0 mol%;
[0153] More preferably wherein M comprises:
[0154] -Ni with content x, where 50.0mol%≤x≤80.0mol%,
[0155] - Mn with a content of y, wherein 10.0mol%≤y≤25.0mol%,
[0156] -Co with content z, where 10.0mol%≤z≤25.0mol%,
[0157] - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O,
[0158] - wherein x+y+z+a is 100.0 mol%;
[0159] More preferably wherein M comprises:
[0160] -Ni with content x, where 55.0mol%≤x≤75.0mol%,
[0161] - Mn with a content of y, where 12.5mol%≤y≤22.5mol%,
[0162] -Co with content z, where 12.5mol%≤z≤22.5mol%,
[0163] - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O,
[0164] - wherein x+y+z+a is 100.0 mol%;
[0165] Most preferably wherein M comprises:
[0166] -Ni with content x, where 55.0mol%≤x≤70.0mol%,
[0167] - Mn with a content of y, wherein 15.0mol%≤y≤22.5mol%,
[0168] -Co with content z, where 15.0mol%≤z≤22.5mol%,
[0169] - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O,
[0170] - wherein x+y+z+a is 100.0 mol%.
[0171] As known to those skilled in the art, the NMC cathode active material may contain impurities, or be doped or coated, resulting in the total cathode active material containing one or more elements other than Li, Ni, Mn, Co and O, which is reflected in the parameter "D" used herein. In a preferred embodiment of the present invention, D is an element selected from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, Zr and Zn; preferably Al, B, Cr, Nb, S, Si, Ti, Y, Zr and W; more preferably B, Nb, Ti, Zr and W.
[0172] Examples of suitable cathode active materials are NMC532, NMC622, NMC 811, preferably NMC622 or NMC811, more preferably NMC622.
[0173] Other composite cathode components
[0174] The present invention has no particular limitations on the additional materials used in the composite cathode. Any suitable additives known to those skilled in the art may be included.
[0175] The optional but preferred additional component of the composite cathode of the present invention is a conductive aid, particularly a carbon-based conductive aid. The carbon-based conductive aid can be any carbon-rich material, such as any material comprising at least 95% by weight carbon, preferably any material comprising at least 99% by weight carbon. Examples of suitable materials are graphite, carbon black, carbon fiber, carbon nanotubes, graphene and combinations thereof. Carbon black is known to those skilled in the art and includes variants such as acetylene black or super C65.
[0176] In a preferred embodiment, the carbon-based conductive aid as described herein is present in the solid composite cathode of the present invention in an amount of at least 0.5 wt % (based on the combined weight of the polymer electrolyte and the cathode active material), preferably at least 1 wt % (based on the combined weight of the polymer electrolyte and the cathode active material), and more preferably at least 3 wt % (based on the combined weight of the polymer electrolyte and the cathode active material). Typically, the carbon-based conductive aid is present in an amount of less than 12 wt % (based on the combined weight of the polymer electrolyte and the cathode active material), preferably less than 9 wt % (based on the combined weight of the polymer electrolyte and the cathode active material), and more preferably less than 7 wt % (based on the combined weight of the polymer electrolyte and the cathode active material).
[0177] Another optional but preferred additional component of the composite cathode of the present invention is a binder. In some embodiments of the present invention, the solid composite cathode of the present invention further comprises a binder, such as a polymer binder. The binder is not particularly limited, and the binder can be any suitable polymer binder, such as polyimide (PI), polyvinylidene chloride (PVdC), polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), etc.
[0178] Method for preparing the composite cathode of the present invention
[0179] As explained herein before, in some embodiments of the present invention, the composite cathode comprises a homogeneous mixture of cathode active material particles and polymer electrolyte particles. Therefore, in another aspect of the present invention, a method for producing a composite cathode is provided, the method comprising the steps of:
[0180] (a1) providing a cathode active material in a particle form, the cathode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co;
[0181] (b1) providing a polymer electrolyte as described herein in particle form;
[0182] (c1) blending the cathode active material of step (a) and the polymer electrolyte of step (b) into a uniform blend; and
[0183] (d1) Optionally, compacting the blend obtained in step (c).
[0184] As explained previously herein, in some embodiments of the present invention, the cathode active material is porous and the polymer electrolyte is coated on and / or at least partially embedded in the cathode active material. Therefore, in another aspect of the present invention, a method for producing a composite cathode is provided, the method comprising the steps of:
[0185] (a2) providing a cathode active material, the cathode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co;
[0186] (b2) providing a precursor composition as described herein;
[0187] (c2) contacting the precursor composition with the cathode active material; and
[0188] (d2) polymerizing the precursor composition in the presence of the cathode active material.
[0189] The embodiments described in this disclosure in connection with the composite cathode of the present invention apply mutatis mutandis to the method of preparing the composite cathode. For example, the various embodiments relating to the properties and amounts of monomers, crosslinkers, initiators, electrolyte compositions as explained herein in the context of the composite cathode are equally applicable to the method of preparing the composite cathode.
[0190] In a preferred embodiment of the method for preparing a composite cathode, wherein the polymer electrolyte is coated on and / or at least partially embedded in the cathode active material, the precursor composition comprises one or more free radical initiators as described herein before, and step (d2) comprises activating the free radical initiator. Activation is preferably carried out by UV irradiation of the precursor composition or by heating the precursor composition to a temperature of at least 50°C, preferably at least 60°C. Preferably, step (d2) is carried out under an inert gas atmosphere, preferably an inert atmosphere, such as nitrogen or argon. The contacting of step (c2) may include mixing and / or depositing the precursor composition on the surface of the cathode active material. The contacting of step (c2) is preferably carried out for at least 1 minute before polymerization so that sufficient mixing or impregnation can be achieved. In this way, a composite cathode comprising a polymer electrolyte and a cathode active material of the present invention can be obtained.
[0191] Electrochemical cell comprising the composite cathode of the present invention
[0192] In another aspect of the invention, there is provided an electrochemical cell comprising the composite cathode of the invention.
[0193] The embodiments described in this disclosure relating to composite cathodes are applicable to electrochemical cells comprising composite cathodes mutatis mutandis. For example, various embodiments relating to the properties and amounts of monomers, crosslinkers, initiators, electrolyte compositions as explained herein in the context of composite cathodes are equally applicable to electrochemical cells comprising composite cathodes.
[0194] The electrochemical cell preferably comprises an anode, a composite cathode of the present invention, and an electrolyte. In some embodiments, the electrolyte comprises or consists of a polymer electrolyte identical to the polymer electrolyte contained in the composite cathode. The polymer electrolyte described herein has a gel-like consistency and is considered to be a solid electrolyte for the purposes of the present disclosure. As will be appreciated by those skilled in the art, it can also be used as a separator in an electrochemical cell. For example, an electrochemical cell may comprise an anode, a cathode composite of the present invention, and a separator, which is a polymer electrolyte identical to the polymer electrolyte contained in the cathode composite of the present invention. As will be appreciated by those skilled in the art, in order to function as a separator, a portion of the solid polymer electrolyte separating the anode and the composite cathode should be substantially free of cathode active material.
[0195] The anode comprises an anode active material. Suitable electrochemically active anode materials are those known in the art. For example, the anode may comprise graphite carbon, metallic lithium, or a metal alloy comprising lithium as the anode active material. The anode comprises an electrode active material different from the cathode active material contained in the composite cathode of the present invention.
[0196] In particularly preferred embodiments, the cathode active material described herein is the only cathode active material contained in the cathode of an electrochemical cell.
[0197] The electrochemical cell as described herein is preferably a lithium ion containing cell, wherein the charge transport is controlled by Li + Ion impact. The electrochemical cell may have a disc or prismatic shape. The electrochemical cell may include a housing that may be made of steel or aluminum. Multiple electrochemical cells may be combined into an all-solid-state battery having both solid electrodes and solid electrolytes.
[0198] Method for preparing the electrochemical cell of the present invention
[0199] In another aspect, the present invention provides a method for producing an electrochemical cell comprising the steps of:
[0200] (a) providing a composite cathode as described herein,
[0201] (b) providing an anode,
[0202] (c) providing electrolytes,
[0203] (d) forming an electrochemical cell by assembling the cathode, the anode and the polymer electrolyte into the electrochemical cell.
[0204] The embodiments described in the present disclosure relating to electrochemical cells or composite cathodes apply mutatis mutandis to methods of preparing electrochemical cells. For example, various embodiments relating to the properties and amounts of monomers, crosslinkers, initiators, electrolyte compositions as explained herein in the context of composite cathodes are equally applicable to methods of preparing electrochemical cells.
[0205] Use of the composite cathode of the present invention
[0206] In another aspect of the invention there is provided the use of a composite cathode as described herein as a cathode for an electrochemical cell.
[0207] The embodiments described in the present disclosure relating to composite cathodes apply mutatis mutandis to the use of composite cathodes. For example, the various embodiments relating to the properties and amounts of monomers, crosslinkers, initiators, electrolyte compositions as explained herein in the context of composite cathodes are equally applicable to the use of composite cathodes.
[0208] The electrochemical cell is preferably an electrochemical cell as described herein in the context of another aspect of the invention.
[0209] Secondary battery comprising the electrochemical cell of the invention and use thereof
[0210] In another aspect, the present invention relates to a battery, more particularly a lithium ion battery or a lithium metal battery, comprising at least one electrochemical cell comprising a composite cathode of the present invention, such as two or more electrochemical cells as described herein.
[0211] The electrochemical cells as described herein can be combined with each other, for example connected in series or in parallel. Series connection is preferred. The electrochemical cells or batteries described herein can be used to manufacture or operate automobiles, computers, personal digital assistants, mobile phones, watches, camcorders, digital cameras, thermometers, calculators, laptop BIOS, communication equipment, satellite or remote car locks, and fixed applications, such as energy storage devices for power plants.
[0212] In another aspect of the invention is a method of manufacturing or operating an automobile, computer, personal digital assistant, mobile phone, watch, camcorder, digital camera, thermometer, calculator, laptop BIOS, communication equipment, satellite, remote car lock, and stationary applications (such as energy storage devices for power plants) by using at least one battery or at least one electrochemical cell as described herein (including the composite cathode of the invention).
[0213] Another aspect of the invention is the use of an electrochemical cell or battery as described herein (comprising a composite cathode of the invention) in a motor vehicle, a bicycle operated by an electric motor, a robot, an aircraft (e.g. an unmanned aerial vehicle including a drone), a ship, a satellite or a stationary energy storage.
[0214] Another aspect of the invention is a method of providing power to a device, wherein the power is supplied by an electrochemical cell or battery as described herein comprising a composite cathode of the invention, wherein the electrochemical cell or battery (preferably an electrochemical cell) as described herein operates at a voltage above 4.4 V, preferably above 4.5 V, more preferably above 4.6 V, such as above 4.7 V. These devices may be any battery powered device, but are preferably selected from motor vehicles, computers, personal digital assistants, mobile phones, watches, camcorders, digital cameras, thermometers, calculators, laptop BIOS, communication devices, satellites, remote car locks, stationary applications (such as energy storage devices for power plants), bicycles operated by electric motors, robots, aircraft (e.g. unmanned aerial vehicles including drones), ships, satellites, etc.
[0215] The invention further provides a device comprising at least one battery or electrochemical cell as described herein (comprising the composite cathode of the invention). Preferred are mobile devices, such as vehicles, for example cars, bicycles, aircraft, satellites or water vehicles, such as ships or boats. Other examples of mobile devices are those portable devices, for example computers, especially laptops, telephones or power tools, for example from the construction sector, especially drills, battery-driven screwdrivers or battery-driven nailers.
[0216] Example
[0217] 1. Preparation of Materials
[0218] The electrolyte composition composed of a deep eutectic solvent (DES) was prepared by mixing lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and N-methylacetamide in a 1:4 molar ratio under vigorous stirring until a homogeneous transparent liquid was obtained. The precursor composition was prepared as follows: the monomers shown in Table 1, the cross-linkers shown in Table 1, and the free radical initiators shown in Table 1 were mixed into a premix with a (monomer: cross-linker): initiator molar ratio of (90:10):5, and DES was combined with the premix at a DES: premix volume ratio of 85:15. The resulting mixture was stirred to obtain a homogeneous blend and polymerized by UV irradiation (365 nm) for 1 hour.
[0219] The cathode (LiNi 0.6 Mn 0.2 Co 0.2 O2) with 80 wt% LiNi 0.6 Mn 0.2 Co 0.2 O2, 10 wt% carbon black and 10 wt% poly(vinylidene fluoride) (PVDF) were prepared by mixing them in N-methyl-2-pyrrolidone (NMP). The well-mixed slurry was cast on aluminum foil and dried at 110 °C in air to obtain a film with a thickness of about 18.7 µm and a surface area of 0.622 mg cm -2 The active material loading of the electrode (0.109 mAh cm -2 , assuming that the theoretical capacity of NMC622 is 175 mAh g -1 ).
[0220] For use in button cells, the polymer electrolyte and cathode were cut to size by a hollow punch. The Li|Polymer Electrolyte|NMC622 cell was assembled by placing the cathode in front of a Li foil anode separated by a polymer electrolyte in between.
[0221] Table 1
[0222] 2. Determination of electrochemical properties
[0223] Ionic conductivity was determined by electrochemical impedance spectroscopy (EIS) (using Biologic SP-300) in a symmetrical stainless steel|electrolyte|stainless steel Swagelok type cell at the indicated temperature by perturbing the open circuit potential with an AC sinusoidal potential of 10 mV amplitude in the frequency range of 10 kHz-100 mHz.
[0224] The electrochemical compatibility of the polymer electrolyte with the high voltage cathode material was investigated by electrochemical impedance spectroscopy (EIS) of a NMC622|polymer electrolyte|NMC622 symmetric cell.
[0225] The anodic stability limit was determined by linear sweep voltammetry (using Bio-Logic, SP-300) of the polymer electrolyte sandwiched between a stainless steel working electrode, a lithium metal reference electrode, and a counter electrode in a coin cell setup, where the voltage at the working electrode was swept from the open circuit potential to 6 V vs Li in the anodic scan. + / Li, scan rate 10mV s -1 The stability limit is determined as the onset of electrolyte oxidation, which can be observed by a sudden increase in the measured current. Without wishing to be bound by any theory, the inventors believe that electrolyte oxidation may originate from oxidation of the TFSI anion.
[0226] The cycling performance of the Li|polymer electrolyte|NMC622 battery prepared as described above was measured using a TOYO battery cycler. + / Li and 4.3V vs.Li + The cells were subjected to an open circuit potential (OCP) period of 16 h before galvanostatic cycling between C / 20 and Li. + / Li and 4.3V vs Li + The electrodes were activated by two galvanostatic charge / discharge cycles between 1.5 and 2.5 Nm / Li. The cycling scheme consisted of 5 cycles at C rates of C / 20, C / 10, C / 5, C / 2, 1C, followed by 100 cycles at C / 10. The capacity values were normalized to the weight of the cathode active material (NMC) and the results were verified for reproducibility.
[0227] 3. Results
[0228] The electrochemical characterization results of the polymer electrolyte used in the composite cathode of the present invention are shown in Figures 1 to 20and Table 2. Table 2 shows the excellent ionic conductivity of the polymer electrolyte used in the composite cathode according to the present invention at three different temperatures. Table 2 also highlights the compatibility of the polymer electrolyte used in the composite cathode of the present invention with the NMC622 cathode active material, as can be seen in particular from Figures 17 to 20 (Show Cycle Performance) Exported.
[0229] Table 2 also shows high anode stability values measured in specific Examples 1, 2, 7, and 8, indicating that they can operate at high voltages.
[0230] Figures 9 to 16 The EIS results of the NMC622|polymer electrolyte|NMC622 symmetric cell are shown. For the polymer electrolyte used in the composite cathode of the present invention, the charge transfer resistance Rct does not increase significantly, which means that the NMC622|polymer electrolyte interface is chemically stable. In contrast, for the comparative example, it can be seen that the polymer electrolyte is incompatible with NMC622.
[0231] Figures 17 to 20 The cycling capacity of the Li|polymer electrolyte|NMC622 cell is shown, illustrating the excellent compatibility of the polymer electrolyte of the present invention with high potential cathode materials such as NMC622.
[0232] Table 2
[0233] The polymer electrolytes of Examples 1 to 8 were found to be self-supporting and exhibit good mechanical flexibility.
[0234] 4. Composite cathode synthesis and characterization
[0235] An electrolyte composition consisting of a deep eutectic solvent (DES) was prepared by mixing lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and N-methylacetamide in a 1:4 molar ratio under vigorous stirring until a homogeneous transparent liquid was obtained. The precursor composition was prepared as follows: the monomers shown in Table 3, the cross-linkers shown in Table 3, and the free radical initiators shown in Table 3 were mixed into a premix with a (monomer: cross-linker): initiator molar ratio of (90:10):5, and DES was combined with the premix at a DES: premix volume ratio of 85:15.
[0236] The cathode (LiNi 0.6 Mn 0.2 Co 0.2 O2) with 80 wt% LiNi 0.6 Mn 0.2 Co 0.2O2, 10 wt% carbon black and 10 wt% poly(vinylidene fluoride) (PVDF) were prepared by mixing them in N-methyl-2-pyrrolidone (NMP). The well-mixed slurry was cast onto an aluminum foil and dried at 110°C in air to obtain an electrode.
[0237] An impregnated composite cathode (Example 9) was prepared by drop casting the precursor composition on top of the NMC622 electrode and allowing it to impregnate the pores of the electrode. This was followed by 1 hour of UV curing (365 nm) to form the impregnated electrode. The NMC622 impregnated electrode | polymer electrolyte | NMC622 impregnated electrode cell was assembled using the polymer electrolyte layer as a separator between the symmetrical impregnated electrodes. The polymer electrolyte was prepared by polymerizing the same precursor composition in the absence of the cathode material.
[0238] A comparative cell (Example 10) was prepared using unimpregnated electrodes.
[0239] The ionic conductivity was determined by electrochemical impedance spectroscopy (EIS) of a symmetrical cell (using Biologic SP-300) at the specified temperature by perturbing the open circuit potential with an AC sinusoidal potential of 10 mV amplitude in the frequency range of 10 kHz-100 mHz.
[0240] Table 3
[0241] Fig.21 Shown is the EIS characterization of the NMC622 impregnated electrode | polymer electrolyte | NMC622 impregnated electrode cell. Fig. 22 A comparative example of EIS characterization of a NMC622|polymer electrolyte|NMC622 cell is shown. It can be seen that impregnation of the polymer electrolyte into the pores of the NMC622 electrode does not result in a significant increase in charge transfer resistance, indicating that the composite cathode of the present invention will yield good performance.
Claims
1. A composite cathode comprising a cathode active material and a polymer electrolyte, wherein the cathode active material comprises Li, M and O, wherein M comprises Ni and one or both of Mn and Co, wherein the polymer electrolyte comprises an electrolyte composition and a polymer network, wherein the electrolyte composition comprises a deep eutectic solvent (DES), wherein the polymer electrolyte is obtainable by polymerizing a precursor composition comprising the electrolyte composition and a first monomer according to formula (I) in R 1 represents a first substituent having 1 to 8 carbon atoms and optionally comprising at least one functional group selected from alcohol, amine, ether, ketone, amide, acetal, ketal, aminoacetal, hemiaminal ether or a combination thereof, preferably wherein R 1 Selected from C1-C6 alkyl, C1-C6 hydroxyalkyl, -(CH2-CH2-O) n -H; and Where R 2 represents H or a second substituent having 1 to 8 carbon atoms and comprising at least one functional group selected from alcohol, amine, ether, ketone, amide, acetal, ketal, aminoacetal, hemiaminal ether or a combination thereof, preferably wherein R 2 Selected from H, C1-C6 alkyl, C1-C6 hydroxyalkyl, -(CH2-CH2-O) n -H; Where R 3 is selected from H, methyl or ethyl; and wherein n is an integer from 1 to 5. 2 . The composite cathode of claim 1 , comprising a homogeneous mixture of cathode active material particles and polymer electrolyte particles.
3. The composite cathode of claim 1, wherein the cathode active material is porous, and wherein the polymer electrolyte is coated on and / or at least partially embedded in the cathode active material. 4 . The composite cathode according to claim 3 , which is obtainable by contacting the precursor composition with the cathode active material and polymerizing the precursor composition in the presence of the cathode active material.
5. A composite cathode according to any one of the preceding claims, wherein the first monomer is according to option A, B or C: AR 1 Selected from C1-C6 alkyl, preferably R 1 is a C3 alkyl group, and R 2 Selected from H or methyl, preferably R 2 is H, and R 3 Selected from H or methyl, preferably R 3 is H; or BR 1 Selected from C1-C6 alkyl, preferably R 1 is a C2 alkyl group, and R 2 Selected from C1-C6 alkyl, preferably R 2 is a C2 alkyl group, and R 3 Selected from H or methyl, preferably R 3 is H; or CR 1 Selected from C1-C6 hydroxyalkyl, preferably R 1 is 2-hydroxyethyl, R 2 Selected from H or methyl, preferably R 2 is H, and R 3 Selected from H or methyl, preferably R 3 It's H.
6. The composite cathode of any preceding claim, wherein the precursor composition further comprises a first cross-linking agent.
7. The composite cathode of claim 6, wherein the first crosslinking agent is selected from a crosslinking agent comprising two or more functional groups selected from the group consisting of allyl (-CH3-CH=CH2), oxirane (-C2H3O), glycidyl (-CH2-C2H3O), vinyl ether (-O-CH=CH2), vinyl ester (-C(O)-O-CH=CH2), vinyl amide (-C(O)-NH-CH=CH2), vinyl amine (-NH-CH=CH2), norbornene, maleate, fumarate, itaconate, alkynyl (-C≡CH), styrene (-Ph-CH=CH2), acrylamide (-NH-CH=CH2), C(O)-CH=CH2), methacrylamide (-NH-C(O)-C(CH3)=CH2), acrylate (-OC(O)-CH=CH2), methacrylate (-OC(O)-C(CH3)=CH2) and combinations thereof, preferably the first crosslinking agent is selected from a crosslinking agent containing two or more functional groups selected from the following: acrylamide (-NH-C(O)-CH=CH2), methacrylamide (-NH-C(O)-C(CH3)=CH2), acrylate (-OC(O)-CH=CH2), methacrylate (-OC(O)-C(CH3)=CH2) and combinations thereof.
8. The composite cathode of any preceding claim, wherein the deep eutectic solvent (DES) has a eutectic point less than or equal to 25°C.
9. The composite cathode according to any one of the preceding claims, wherein the deep eutectic solvent (DES) comprises at least one hydrogen bond acceptor and at least one hydrogen bond donor, wherein the at least one hydrogen bond acceptor comprises a lithium salt, a zinc salt or a combination thereof, preferably a lithium salt.
10. The composite cathode of claim 9, wherein the at least one hydrogen bond acceptor is selected from the group consisting of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium chloride (LiCl), lithium hexafluorophosphate (LiPF6), lithium polysulfide, lithium perchlorate (LiClO4), lithium bromide (LiBr), lithium iodide (LiI), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(oxalato)borate (LiBOB), lithium fluoroalkyl phosphate (LFAP [LiPF3(CF2CF3)3]), and combinations thereof, preferably lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and wherein preferably the at least one hydrogen bond donor is selected from the group consisting of: urea, N-methylurea, N,N-dimethylurea, N,N'-dimethylurea, N,N,N'-trimethylurea, thiourea, N-methylthiourea, N,N-dimethylthiourea, N,N'-dimethylthiourea, N,N,N'-trimethylthiourea, ethylene glycol, propane-1,2-diol, propane-1,3-diol, butane-1,4-diol, 1,2,3-propanetriol, acetic acid, oxalic acid, Malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, benzoic acid, glycolic acid, citric acid, 2-hydroxypropionic acid, 2-hydroxyisobutyric acid, o-phenylenediamine, choline chloride, acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, benzamide, benzenesulfonic acid, p-toluenesulfonic acid, o-toluenesulfonic acid, m-toluenesulfonic acid and combinations thereof, preferably N-methylacetamide.
11. A composite cathode according to any one of the preceding claims, wherein the cathode active material comprises Li, M and O, wherein M comprises: - Nickel content x, where 50.0 mol % ≤ x ≤ 95.0 mol %, preferably where 55.0 mol % ≤ x ≤ 95.0 mol %, - Mn with a content of y, where 0.0mol%≤y≤40.0mol%, -Co with content z, where 0.0mol%≤z≤40.0mol%, - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O, - wherein x+y+z+a is 100.0 mol%; Preferably wherein M comprises: -Ni with content x, where 50.0mol%≤x≤85.0mol%, - Mn with a content of y, where 7.5mol%≤y≤25.0mol%, -Co with content z, where 7.5mol%≤z≤25.0mol%, - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O, - wherein x+y+z+a is 100.0 mol%; More preferably wherein M comprises: -Ni with content x, where 50.0mol%≤x≤80.0mol%, - Mn with a content of y, wherein 10.0mol%≤y≤25.0mol%, -Co with content z, where 10.0mol%≤z≤25.0mol%, - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O, - wherein x+y+z+a is 100.0 mol%; More preferably wherein M comprises: -Ni with content x, where 55.0mol%≤x≤75.0mol%, - Mn with a content of y, where 12.5mol%≤y≤22.5mol%, -Co with content z, where 12.5mol%≤z≤22.5mol%, - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O, - wherein x+y+z+a is 100.0 mol%; Most preferably wherein M comprises: -Ni with content x, where 55.0mol%≤x≤70.0mol%, - Mn with a content of y, wherein 15.0mol%≤y≤22.5mol%, -Co with content z, where 15.0mol%≤z≤22.5mol%, - D with a content a, where 0.0 mol%≤a≤2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co and O, - wherein x+y+z+a is 100.0 mol%.
12. A method for producing a composite cathode according to any one of the preceding claims, the method comprising the steps of: (a1) providing a cathode active material in a particle form, the cathode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co; (b1) providing a polymer electrolyte according to any one of the preceding claims in particle form; (c1) blending the cathode active material of step (a) and the polymer electrolyte of step (b) into a uniform blend; and (d1) optionally, compacting the blend obtained in step (c).
13. A method for producing a composite cathode according to any one of claims 1 to 11, the method comprising the steps of: (a2) providing a cathode active material, the cathode active material comprising Li, M and O, wherein M comprises Ni and one or both of Mn and Co; (b2) providing a precursor composition according to any one of the preceding claims; (c2) contacting the precursor composition with the cathode active material; and (d2) polymerizing the precursor composition in the presence of the cathode active material.
14. Use of a composite cathode according to any one of claims 1 to 11 as a component of an electrochemical cell.
15. An electrochemical cell comprising an anode and a composite cathode according to any one of claims 1 to 11.
Citation Information
Patent Citations
Deep Eutectic Solvent-Based Gel Polymer Electrolytes
US20200343586A1